Identification the Gene Nucleotide Sequence of Outer Membrane Protein Aeromonas Hydrophilla Bacteria from East Java Local Isolates Using Polimerase Chain Reaction - Yuliani, M. Gandul Atik; Handijatno, Didik; Madyawati, Sri Pantja (KnE Life Sciences, 2017)
Aeromoniasis disease or known Ulcer Diseases caused by Aeromonas hydrophila which in fish or shrimp often occurs in some embankment or in the Aquarium can cause sign patches – patches of bleeding can even cause economic loss and death if not promptly treated with treatment that accompanied the good sanitation. This disease affects many farmed freshwater fish in East Java. Previous research has managed to do the characterization of antigenic protein originating from the OMP (outer membrane protein) Aeromonas hydrophilla. Because it is felt necessary to do DNA sequensing encoder protein in question.To achieve these goals then do some exploratory research laboratoric methods, namely: identification of the bacterium Aeromonas hydrophilla fish from suspect infection by PCR, gel electrophoresis and Sequencing of gene fragments of the agarosa OMP A. hydrophilla isolates of East Java. The results obtained from this research is the result of agarosa gel electrophoresis in DNA chromosome Aeromonas hydrophila bacteria cells is carried out at a temperature of annealing 54oC position 400 bp and the results of the sequencing primer that is used produces a sequence of nucleotides is around 355 nucleotides. Key words: Aeromonas hydrophilla, agarosa gel electrophoresis, DNA sequencing